POLYNOMIAL SOLUTIONS OF ALGEBRAIC ORDINARY DIFFERENTIAL EQUATIONS. III - Gorbuzov, V. N. (Matematichki Bilten, 1995)
The building of polynomial solutions on the whole of algebraic differential equations are considered.